"Nobody really gets it";: a qualitative exploration of youth mental health in deprived urban areas. - SMYTH, BOBBY (My University, 2014)
Aim: To explore and describe the experience of mental health and addiction for young people living in urban deprived areas in Ireland. Method: Semi-structured qualitative interviews were conducted with 20 young adults attending health and social care agencies in two deprived urban areas, and analysed using thematic analysis. Results: Five main themes were identified: experiencing symptoms, symptom progression, delay accessing help, loss of control/crisis point, and consequences of mental health and substance use issues. As young people delayed help, symptoms disrupted normal life progression and they found themselves unable to engage in every-day activities. Living in deprivation made it harder to avoid developing problems: many had added stressors, less familial support and early exposure to violence, addiction and bereavement. Conclusion: Young people in urban deprived areas are vulnerable to mental health and addiction issues. Early identification is necessary to halt this progression to improve their chances of achieving their potential
PUBLISHED
Keywords: substance addiction